Effect of magnetic field on heat transfer from a channel: Nanofluid flow and porous layer arrangement. (December 2021) - Farahani, Somayeh Davoodabadi; Amiri, Mohammad; Majd, Behnam Kazemi; Mosavi, Amir
Abstract: Due to the high number of porous media applications in industries, the demands for analyzing the porous medium's flow and heat transfer are rising every day. The present research intends to evaluate the impact of porous media, nanofluid, and magnetic field on heat transfer of a circular channel. Two typical porous arrangements are considered: central configuration and boundary configuration. It is of interest to know the impact of porosity, thickness, permeability, and thermal conductivity ratio in porous media. The working fluid, nanoparticles and porous medium are water, CuO and steel foam, respectively. The results reveal that the heat transfer rate in the central arrangement is more than the boundary arrangement. When the non-dimensional thickness of the porous media is 0.8 in the central arrangement, the heat transfer rate is at its peak. Simultaneously, the minimum happens when the non-dimensional thickness is set to 0.6 in the boundary arrangement. Applying nanofluid and increasing the volume fraction will improve the heat transfer rate. The average heat transfer coefficient is increased when the magnetic field is applied up to the intensity of 0.5 T. Additionally, the maximum heat transfer enhancement is achieved when the thickness is 0.6 in boundary arrangement in the case of applying the magnetic field, which is estimated to be 3–5% more. Modifying the shape of the porous media in the boundary arrangement decreases the heat transfer rate about 7–21%, depending on the shape compared to a homogeneous boundary porous.